(untitled) (Bangladesh Journal of Agricultural Research, 2014)
A study was conducted to estimate the productivity gap in MV T.Aus rice between potential farm and actual farm as well as examine the factors responsible for MV T.Aus rice yield gaps in Chuadanga. In the Aus season, 80 demonstration plots managed by Department of Agriculture Extension and 80 farmers managed plots were selected from four villages of Chuadanga sadar upazila. Data were collected in two phases using structured questionnaire. Both tabular and statistical techniques were employed for analyzing the data. The analysis has further been extended to estimate the contribution of individual technical factors to the yield and the input-output relations. The average yield of MV Aus rice were 2.84 t/ha and 3.31 t/ha in the farmers plots and demonstration plots, respectively, indicating 17% yield gain in the demonstration plots. The production cost per hectare on full cost and cash cost basis were 16 and 1% higher, respectively, in the demonstration plots than that in the farmers plots. But the unit cost of production on full cost and cash cost basis were lower 0.60 and 15%, respectively, in the demonstration plots than that in the farmers plots. The benefit cost ratio (BCR) was also higher on full cost and cash cost basis in the demonstration plots compared to farmers plot. Analysis further indicated that there is ample scope of increasing modern Aus yield by 0.29 t/ha through adopting appropriate variety, timely sowing and proper irrigation as well as weeding at the farm level. DOI: http://dx.doi.org/10.3329/bjar.v38i4.19664 Bangladesh J. Agril. Res. 38(4): 733-747, December 2013